PENGARUH MEDIA POWER POINT POWTOON TERHADAP KEMAMPUAN MENGHAFAL HURUF HIRAGANA SISWA KELAS X SMAN 1 TELUK KUANTAN - Santika, Sari; Basri, Merri Silvia; Widiati, Sri Wahyu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: High school students studying Japanese must master Hiragana as a basis for learning. This skill is very important because real Japanese words, such as names of places and things, are written in Hiragana. Hiragana is taught before katakana and kanji, especially in the early stages of learning in high school. Understanding Japanese characters becomes the main goal of teaching, facilitating Japanese language learning. Quasi-experimental was used by the researcher as the methodology in this study. This strategy was used because it suited the characteristics of the research sample, which consisted of a comparison group or control group and an experimental group. The determination of the experimental and control groups was predetermined and not based on random selection, in accordance with the nonequivalent control group design (Sugiyono, 2014). In accordance with the findings of the Mann-Whitney Test, the value of Asymp. Sig (2-tailed) of 0.000 is smaller than 0.05. This shows that Power point powtoon has a significant influence on the ability of class X students of SMAN 1 Teluk Kuantan in memorizing Hiragana letters. The conclusion of this study is that the use of Power point powtoon media has a positive effect on the ability of class X students of SMAN 1 Teluk Kuantan in memorizing Hiragana letters. Although there are some data that are not normally distributed, the Mann-Whitney Test shows a significant value, supporting that the influence of the media is quite large. Students who used powtoon showed improvement in articulating the letters and the ability to memorize Hiragana letters.Key words: Power point, Powtoon, Experiment, Hiragana